SCREENING KLON-KLON HASIL SELEKSI BAWANG MERAH (Allium ascalonicum L.)PADA MUSIM PENGHUJAN TERHADAP HASIL DI DESA KLAMPOK KABUPATEN BREBES CLONES SCREENING RESULTED FROM SHALLOT (Allium ascalonicum L.) SELECTION IN THE RAINY SEASON ON YIELD AT KLAMPOK VILLAGE BREBES REGENCY - Putrasamedja, Sartono (Pembangunan Pedesaan, 2010)
The purpose of this experiment is to know clone-resistant and better production than the screening results of shallot (Allium ascalonicum L.) clone selection in the rainy season. Ten clones were used, i.e., clone no. 1 to 10, local cultivars and Yellow Bima Brebes as controls. The experiments were carried out at the farmer garden in Klompok Brebes, Central Java. The soil was Aluvial with pH 5.6 to 6.2 at an altitude of approximately 4 meters above sea level started from December 2008-March 2009. The method used was randomized design with 12 treatment groups repeated 3 times using spacing of 15 Ã 20 cm. The results showed that clones no. 6 was able to survive, grow well, and produce the highest yield in the rainy season with a production of 7.78 tons -1 ha . These clones still could be improved when the plant was cultivated at a proper planting season.